A REVIEW ON DESIGN AND DEVELOPMENT OF CHAIRLESS CHAIR BY USING DAMPER - Rahul B. Madane; Shahaji M. Pawar; Rajkumar B. Rede Patil; Ramesh M. Raste; Somnath M. Pise; Mayur D. Jagtap (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
It is very difficult to stand and work for overall shift in the company by a worker. This will reduce the efficiency of the worker. The solution to this problem is to have a portable device which has an ergonomic design, low cost exoskeletons. In this work a mechanical ergonomics device that is designed around the shape and function of the human body, with segments and joints corresponding to those of the person it is externally coupled with. It functions as a chair whenever it is needed and is coined as Chair less Chair. Worker in industrial can wear it on legs like an exoskeleton. It locks into place and you can sit down on it. The device never touches the ground, which makes it easier to wear: a belt secures it to the hips and it has straps that wrap around the thighs. These are specially designed and part of the mechanism, but an alternate version works with any footwear and touches the ground only when in a stationary position. The user just moves into the desired pose. It will fit closely to lower part of the body as an external body part on which maximum body forces act upon. It is a cost effective product and any error in design may fail the structure which creates loss. So, these forces should be carefully analyzed during the design of structure. The best way to predict these forces during pre-manufacturing stage is to make an analysis on the structure with the help of software. This helps in estimating the stresses induced on the structure which is one of the most important criteria for evaluation of the model.